Evaluasi Kandungan Lemak Kasar dan BETN Silase Daun Lamtoro pada Level yang Berbeda Sebagai Bahan Pakan Utama Pakan Komplit - Juwandi, Juwandi; Munir, Munir; Fitriani, Fitriani (Fakultas MIPA UNM, 2018)
Abstract. The purpose of this study was to determine the crude fat content and BETN silage combination of rice straw and lamtoro leaves at different levels as the main feed ingredients for complete feed. This study used a completely randomized design (CRD) with 4 treatment levels and 3 replications namely contro = 100% rice straw (control), 40% = 60% rice straw + 40% lamtoro leaf, 30% = 70% rice straw + 30% lamtoro leaves, 20% = 80% rice straw + 20% lamtoro leaves. The results showed that the mixing of rice straw and lamtoro leaves as a complete feed had a very significant effect on crude fat content and had a significant effect on BETN content. Based on the results and discussion of the study, it can be concluded that feed with a combination of rice straw and lamtoro leaves affects the crude fat content and BETN. Where the treatment of 40% with a combination of 60% rice straw material and 40% leucaena leaves showed the best results for fat content and BETN.Keywords: fat, BETN, rice straw, lamtoro leaf, and silage